2022
DOI: 10.1093/neuonc/noac079.472
|View full text |Cite
|
Sign up to set email alerts
|

NFB-08. TRAM-01: A Phase 2 study of trametinib for pediatric patients with neurofibromatosis type 1 and plexiform neurofibromas

Abstract: BACKGROUND: Plexiform neurofibromas (PN) are found in up to 50% of patients with neurofibromatosis type 1 (NF1). Trametinib has been used widely to treat PN but limited data has been reported on its efficacy within a clinical trial. METHODS: This ongoing multicenter phase II trial includes patients with pediatric low-grade glioma and PN. The primary objective for PN was to evaluate the overall response rate based on RECIST 1.1 criteria after daily oral trametinib administration for eighteen 28-day cycles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Selumetinib has shown promising single-agent activity in this group of patients 9 and has been approved since October 2020 by the FDA and June 2021 by the EMA for the treatment of inoperable symptomatic plexiform neurofibromas (PNs) in children with NF1 . Additionally, trametinib has shown single-agent activity in this population, 10 but has not been approved for this last indication by the FDA or the EMA. Due to initial lack of access to selumetinib until EMA approval in June 2021, trametinib was prescribed for this indication in Europe until that date.…”
Section: Discussionmentioning
confidence: 99%
“…Selumetinib has shown promising single-agent activity in this group of patients 9 and has been approved since October 2020 by the FDA and June 2021 by the EMA for the treatment of inoperable symptomatic plexiform neurofibromas (PNs) in children with NF1 . Additionally, trametinib has shown single-agent activity in this population, 10 but has not been approved for this last indication by the FDA or the EMA. Due to initial lack of access to selumetinib until EMA approval in June 2021, trametinib was prescribed for this indication in Europe until that date.…”
Section: Discussionmentioning
confidence: 99%
“…ERK-dependent target genes are overexpressed in both murine and human PNF, and both MEK and ERK inhibitors have been shown to block PNF growth in vivo [ 45 , 46 ]. Furthermore, multiple phase I and II clinical trials have demonstrated the efficacy of MEK inhibitors (selumetinib, mirdametinib, trametinib, and binimetinib) in the treatment of PNF, resulting in tumor shrinkage, functional benefits, and improvement in patient-reported outcome measures, including pain and quality of life [ 47 , 48 , 49 , 50 , 51 ]. In 2020, the United States Food and Drug Administration (FDA) approved selumetinib for the treatment of symptomatic, inoperable PNF in children 2 years of age and older [ 52 ].…”
Section: Biallelic Loss Of Nf1 In Schwann Cell Pre...mentioning
confidence: 99%